Treatment tactics for complicated esophageal cancer in a patient after lung transplantation - A. L. Akopov; S. Y. Dvoreckiy; A. A. Ilin; S. D. Gorbunkov; A. V. Zinchenko; M. A. Vasilieva; E. V. Blinov; A. A. Khryapa; E. G. Gavrilova; N. A. Yaitsky (Вестник хирургии имени И.И. Грекова, 2022)
We report the clinical case of esophageal cancer development in the patient who previously underwent bilateral lung transplantation. The oncological disease was characterized by extremely rapid growth; despite the regular post-transplant examination, esophageal cancer was diagnosed in IV stage (liver metastases). The tumor was complicated by recurrent massive bleeding. For that reason, according to vital indications, a subtotal esophagectomy with a plasty by wide gastric tube was performed. The postoperative period was uneventful. The postoperative chemotherapy was carried out and stabilization achieved.